Effects of Coadsorbed Oxygen on the Infrared Driven Decomposition of N 2 O on Isolated Rh 5 + Clusters - Hermes, A; Hamilton, S; Hopkins, W; Harding, D; Kerpal, C; Meijer, G; Fielicke, A; Mackenzie, S (American Chemical Society, 2011)
The thermally induced decomposition of nitrous oxide on isolated Rh 5+ and Rh 5O + clusters has been investigated using mid-infrared multiple photon dissociation spectroscopy. The presence of a single coadsorbed oxygen atom is observed to have a profound effect on the cluster surface processes that ensue following infrared heating of the cluster. Exciting the infrared active N 2O bending transition in Rh 5N 2O + results predominantly (≥85%) in molecular desorption of the N 2O moiety, while the same excitation in Rh 5ON 2O + leads instead to N 2O dissociation on the cluster surface producing Rh 5O 2+ (≥85%). Calculations of the reaction pathway using density functional theory indicate that the change in branching ratio arises from a 0.4 eV greater binding energy of N 2O to Rh 5O + compared with Rh 5+, taking the desorption threshold above the reaction barrier for the surface reaction channel whose energy is unchanged.